Artificial intelligence and fintech: An overview of opportunities and risks for banking, investments, and microfinance. (10th May 2021) - Ashta, Arvind; Herrmann, Heinz
Abstract: Artificial Intelligence (AI) is creating a rush of opportunities in the financial sector, but financial organizations need to be aware of the risks inherent in the use of this technology. Financial organizations are integrating AI in their operations: in‐house, outsourced, or ecosystem‐based. The growth of AI‐based fintech firms has encouraged several mergers and acquisitions among financial service providers and wealth managers as they grapple with volatility, uncertainty, complexity, and ambiguity. AI's unique promise of combined cost reduction and increased differentiation makes it generally attractive across the board. However, perhaps other than fraud detection, these benefits depend on the scale of an organization. Risk arises from nonrepresentative data, bias inherent in representative data, choice of algorithms, and human decisions, based on their AI interpretations (and whether humans are involved at all once AI has been unleashed). Risk reduction requires a vigilant division of labour between AI and humans for the foreseeable future.